Dermatoscopy in chromoblastomycosis (Boletin Médico de Postgrado, 2025)
Chromoblastomycosis is a prevalent disease in tropical and subtropical areas of the world. Although it is an entity of worldwide repercussion, the most affected countries are Brazil, Costa Rica, Dominican Republic, Madagascar and Venezuela. During 2016 begins the introduction of dermoscopy as part of the study and knowledge of the pathology and to date there are very few publications about it. Dermoscopy is located as the link between clinical and histological diagnosis. The following is a clinical case corresponding to a 55 year old male patient, dedicated to goat breeding and coming from a semi-arid zone of the Torres Municipality with a current disease of two years of evolution given by an erythematodescamative plaque with sectors covered by crusts, hemorrhagic stippling alternating with areas of scar appearance, located on the posterior face of the left forearm; dermatoscopic, histological and microbiological studies were performed, concluding that it was a case of chromoblastomycosis caused by Cladophialophora carrionii. Chromoblastomycosis is a chronic entity, regularly occurring in scattered rural populations, which limits access to specialized consultations. Accessible and easily transportable diagnostic methods will help in the timely management of this disease.